High efficiency targeting of IFN-α activity: Possible applications in fighting tumours and infections. Issue 2 (April 2015) - Uzé, Gilles; Tavernier, Jan
Abstract In this short review, we summarize how insights into the structure and dynamics of interferon-receptor complex assembly and activation guided the design of a novel class of engineered type I interferons that combine a largely lost potency on non-targeted cells with high activity on targeted cells. These novel interferons are expected to exhibit lower systemic toxicities compared to other interferon therapy modalities and could open avenues to revive these cytokines for the treatment of patients suffering of cancer and viral infections.